2019
DOI: 10.1073/pnas.1820892116
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule factor B inhibitor for the treatment of complement-mediated diseases

Abstract: Dysregulation of the alternative complement pathway (AP) predisposes individuals to a number of diseases including paroxysmal nocturnal hemoglobinuria, atypical hemolytic uremic syndrome, and C3 glomerulopathy. Moreover, glomerular Ig deposits can lead to complement-driven nephropathies. Here we describe the discovery of a highly potent, reversible, and selective small-molecule inhibitor of factor B, a serine protease that drives the central amplification loop of the AP. Oral administration of the inhibitor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
158
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 31 publications
(35 reference statements)
2
158
0
2
Order By: Relevance
“…As the initiating protease of the classical pathway, C1r catalyzes the first proteolytic cleavage event and thus represents the most upstream enzymatic target of the pathway. While complement-directed therapeutics continue to be dominated by antibody-based drugs, small-molecules have recently seen two major breakthroughs in the successful development of factor B and factor D-specific inhibitors [ 48 , 49 , 50 ]. In general, small-molecule drugs are afforded greater tissue penetrance relative to antibodies/biologics and can more easily cross the blood–brain barrier [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the initiating protease of the classical pathway, C1r catalyzes the first proteolytic cleavage event and thus represents the most upstream enzymatic target of the pathway. While complement-directed therapeutics continue to be dominated by antibody-based drugs, small-molecules have recently seen two major breakthroughs in the successful development of factor B and factor D-specific inhibitors [ 48 , 49 , 50 ]. In general, small-molecule drugs are afforded greater tissue penetrance relative to antibodies/biologics and can more easily cross the blood–brain barrier [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given their low molecular complexity, it is not necessarily expected that fragment hits themselves will exhibit high selectivity [ 36 ]. Nonetheless, it is encouraging that active-site targeted small-molecule inhibitors of other complement serine proteases, factor B and factor D, have ultimately overcome this same challenge of specificity [ 48 , 49 , 50 ]. Although our C1r-domain mapping and molecular dynamics studies have provided information about CMP-1696, defining the binding mode of each fragment hit identified here—including CMP-1611 using empirical experimental methods, such as x-ray crystallography coupled with rigorous MD simulations—is a key next step being actively pursued in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Factor B (FB), a trypsin-like serine protease, plays an important role in central amplification of C3b production and circulates as a latent zymogen [38]. During alternative pathway activation, FB first binds to C3b [39].…”
Section: Early Phase Inhibitorsmentioning
confidence: 99%
“…Factor B and Factor D inhibitors are promising therapies for complement-mediated conditions. A recent publication by Schubart et al has demonstrated efficacy in vivo with animal studies and ex vivo with human samples, as indicated by the prevention of hemolysis of PNH erythrocytes [38].…”
Section: Early Phase Inhibitorsmentioning
confidence: 99%
“…LNP023 (Novartis) относится к малым молекулам химического происхождения, основным механизмом действия которого является ингибирование фактора B системы комплемента. Подобно молекулам против фактора D [70], LNP023 предотвращает гемолиз и C3-опсонизацию ПНГ эритроцитов in vitro [71]. В настоящее время проводится клиническое исследование II фазы LNP023 в качестве дополнительной терапии у пациентов с плохим ответом на экулизумаб, проявляющимся повышением ЛДГ > 1,5 раза выше верхней границы нормы [72].…”
Section: ингибиторы проксимальной части комплементаunclassified